Edukasi Dini Siswa SD dalam Mengenal Privasi Tubuh “AKU JAGA, AKU AMAN” - Devi Ayu Kurniawati; Rizka Octivania; Monika Putri; Tatu Fatimah; Nursadi Firmansyah; Ayu Noviyanti (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Community service activities through an early education program on understanding body privacy were conducted by students during the Student Work Program (KKM) at SDN Muncung 1 on August 22, 2024. This program was designed to enhance students' understanding of the importance of maintaining body privacy. The teaching methods employed included lectures, Q&A sessions, discussions, and visual media. This study used a qualitative analysis approach with primary data obtained from photo documentation and secondary data from literature reviews. Survey results showed a significant increase in students' understanding after participating in the activity. The results of this socialization indicate that the interactive approach applied in this program successfully raised awareness about the importance of maintaining body privacy among students and was effective in conveying the material on understanding body privacy. The conclusion of this study emphasizes the importance of using diverse teaching methods and active engagement in learning to create better privacy awareness among students.